2010
DOI: 10.1002/lt.22035
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease in orthotopic liver transplantation: Pretransplant assessment and management

Abstract: The prevalence of coronary artery disease in end-stage liver disease is only now being recognized. Liver transplant patients are a high risk subgroup for coronary artery disease, even if asymptomatic. Coronary artery disease is a predictor of poor outcomes; therefore, identification of those at risk must be a key clinical priority. However, risk assessment is particularly difficult as many of the available diagnostic tools have either proven to be unhelpful or remain to be validated. Risk factor profiling has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 81 publications
2
65
0
Order By: Relevance
“…The mean MELD ranged from 21 to 26 and was highest in the CAD(−) group and lowest in the CADsev group. For all groups, the mean MELD (SD) was 22 (8). There were more male patients in the CADmod (86%) and CADsev (78%) groups compared to the CAD(−) group (67%).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The mean MELD ranged from 21 to 26 and was highest in the CAD(−) group and lowest in the CADsev group. For all groups, the mean MELD (SD) was 22 (8). There were more male patients in the CADmod (86%) and CADsev (78%) groups compared to the CAD(−) group (67%).…”
Section: Resultsmentioning
confidence: 97%
“…Despite the increased prevalence of CAD in LT candidates, there are few studies that have characterized the effect of CAD severity and treatment on the outcome of LT patients (4)(5)(6)(7). Due to the aging of patients with end-stage liver disease (ESLD), an increasing number of older patients on LT waitlists, and limited organ resources, coronary angiography is increasingly advocated to evaluate LT candidates (8)(9)(10) Angiography is often employed in place of noninvasive testing in the evaluation of older and higher risk candidates, as noninvasive tests for myocardial ischemia have varying degrees of reliability in LT candidates (5,(11)(12)(13)(14)(15). To date, no multicenter study has investigated the post-LT survival of patients with angiographically proven obstructive CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 2 recent reviews suggested that dedicated cardiologists should risk-stratify these patients and that a lower threshold for angiography should be considered for patients presenting for OLT because of the physiological state of cirrhosis, although again, overall consensus is lacking. 19,20 These considerations raise the question of how best to minimize such CV events. Prior guidelines and the practice during period A in this study followed traditional cardiac evaluation methods, with stress testing as the primary assessment of risk for noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…End-stage liver disease is associated with increased risk of coronary artery disease. (Ehtisham, 2010). The incidence of coronary artery disease in liver transplant candidates over the age of 50 years has been reported as high as 28%.…”
Section: The Role Of Doppler Echocardiography During Liver Transplantmentioning
confidence: 99%